Implementasi Kaukus dalam Mediasi Berdasar PERMA RI Nomor I Tahun 2016 Perspektif Hakim Mediator Pengadilan Agama Pasuruan - Dakwatul Chairah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
The phenomenon of failure to implement mediation as a modus operandi for divorce settlement in the Religious Courts is because the mediator has not fully used robust mediation techniques in dispute resolution. Caucus techniques as regulated in Perma NO. 1 of 2016 article 14 letter e is a technique that has been used by mediating judges in the Religious Courts. However, mediator judges have various considerations. There are those who do caucus techniques when there is pressure on the parties, do caucus techniques when the parties are less open in disclosing their problems or there is hidden information or do caucus techniques when communication is less conducive. The results of research at the Pasuruan Religious Court, the mediator judges differed in their opinion on the caucus technique in mediation, some said that the caucus technique did not affect the success of the mediation and some were of the opinion that the caucus technique was very effective in reconciling the parties, the implementation of the caucus technique should be done in any mediation. The success rate of implementing the caucus by the mediator judge PA Pasuruan, from 2018 to become a Mediator at the State Religious Court 71% of 24 mediation cases succeeded in peace 19 cases, in 2019, 81% of 31 mediation cases succeeded in peace 26 cases, and in 2020 when they became The mediators at the Pasuruan Religious Court reached 100%. The 14 cases mediated by all of these cases were all successful”.